Online Education Evolution: English Teachers and the Schoology Shift - Dwiniasih, Dwiniasih; Farah Sukmawati Wahidah; Nanda, Deri Sis (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2023)
Integration of technology has penetrated into various fields, including education. With its constant development, technology is always evolving, offering a wide range of applications and sophistication. Accessible to everyone, including teachers, technology raises the question of its acceptance in learning. The goal of this study was to investigate the acceptance of technology in English learning, specifically focusing on the use of Schoology as a platform. Furthermore, it aimed to identify the challenges encountered when integrating it into English learning. The study involved twenty teachers who used Schoology as a supporting medium in the learning process and was conducted through polls and questionnaires. Through this study, the authors aimed to enhance English learning by exploring how technology, specifically Schoology, could be integrated into it. The results provided valuable insights into the acceptance of Schoology among teachers and the challenges faced when integrating it into English learning.